Analisis Kepuasan Pelanggan Atas Kualitas Pelayanan Blackberry Internet Service Provider Telkomsel (Studi Kasus Pada 100 Pengguna Blackberry Internet Service Provider Telkomsel di Kota Semarang) - Citra, Maria; Lubis, Nawazirul; Nurseto, Sendhang (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2014)
Telkomsel is one of the service providers who provide the Blackberry Internet Service. Thisprovider has the largest market share in Indonesia. However, the problem that arises is still the presenceof some customer complaints who use the service pack. The purpose of this study is to determine howmuch the customer satisfaction value toward quality of services in addition to Blackberry InternetService. This study was conducted to 100 Blackberry Internet Service users in the Semarang city. Using aquota sampling technique. The results showed overall satisfaction score is 3.63 it can be concluded thatthe Blackberry Internet Service users in the Semarang city is quite satisfied with the performanceobtained, however, Telkomsel still need to fix the attributes performance score because is still low, theattributes contained the Cartesius chart quadrant A.